2009
DOI: 10.1007/s10198-009-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical penetration of new drug and pharmaceutical market structure in Taiwan: hospital-level prescription of thiazolidinediones for diabetes

Abstract: This study used Taiwan's National Health Insurance claim database (years 2000-2005) to examine how thiazolidinediones (TZD), a new class of drugs for diabetes, penetrated into Taiwan's hospitals, and its association with the concentration of all diabetes drugs at the hospital level. We collected 72 monthly summaries of diabetes prescriptions from all hospitals in Taiwan. Hospital-level pharmaceutical concentration was measured by penetration of TZD, defined as monthly market share of TZD in each hospital. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Exclusivity can have negative effects on the welfare of the society. Market concentration makes it difficult for new products to easily get into the market and thus it decreases the accessibility (16). The lack of exclusivity in the pharmaceutical market in Iran can be considered as a strong point to improve the efficiencies of this section.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusivity can have negative effects on the welfare of the society. Market concentration makes it difficult for new products to easily get into the market and thus it decreases the accessibility (16). The lack of exclusivity in the pharmaceutical market in Iran can be considered as a strong point to improve the efficiencies of this section.…”
Section: Discussionmentioning
confidence: 99%
“…Our results echo Lund et al . 's research findings [13] that patients with advanced cancer are more likely to receive new modality of treatment. However, compared with patients with stage 4 NSCLC, patients with stage 3B NSCLC were more likely to receive MTD (adjusted OR = 1.58; 95% CI = 1.17–2.14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variation in the frequency of prescribing TZD, might have been influenced by pharmaceutical marketing at various levels of healthcare. Tsai et al 21. found that the intense commercial pressures, at different levels of care, influenced the prescription of new, higher‐priced anti‐diabetic drugs, including TZD.…”
Section: Discussionmentioning
confidence: 99%